Advances in research regarding epithelial-mesenchymal transition and prostate cancer - Wei, Xi; Liu, Rui; Li, Wei; Yu, Qi; Yang, Qing Tao; Li, Tao (Frontiers in Cell and Developmental Biology, 2025)
Prostate cancer (PCa) is the most prevalent cancer in men and the fifth leading cause of cancer-related mortality among men globally. Despite substantial advancements in patient prognosis attributable to improvements in PCa treatment, individuals with metastatic castration-resistant prostate cancer continue to experience poor outcomes. Epithelial-mesenchymal transition (EMT) is characterized as a cellular event in which epithelial cells adopt a mesenchymal phenotype while simultaneously losing their epithelial characteristics. EMT has been demonstrated to be associated with the progression of PCa, encompassing tumor metastasis, recurrence, drug resistance, and the development of an immunosuppressive microenvironment. Consequently, this review synthesizes recent studies on EMT in PCa, consolidating the events mediated by EMT in the progression of PCa and the molecular mechanisms linked to EMT activation in this context.